2000
DOI: 10.1136/bmj.320.7230.273
|View full text |Cite
|
Sign up to set email alerts
|

Risk of cardiovascular disease measured by carotid intima-media thickness at age 49-51: lifecourse study

Abstract: Objective To quantify the direct and indirect effects of fetal life, childhood, and adult life on risk of cardiovascular disease at age 49-51 years. Design Follow up study of the "Newcastle thousand families" birth cohort established in 1947. Participants 154 men and 193 women who completed a health and lifestyle questionnaire and attended for clinical examination between October 1996 and December 1998. Main outcome measures Correlations between mean intima-media thickness of the carotid artery (carotid intima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
118
0
3

Year Published

2005
2005
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(125 citation statements)
references
References 28 publications
4
118
0
3
Order By: Relevance
“…If, however, as in the Newcastle 85 þ study, the aim is to assess total diet (foods, energy and a wide range of nutrients), the number of foods included in the FFQ has to be extensive. The European Prospective Investigative Study of Cancer (EPIC) FFQ was chosen as an extensively validated and widely utilized FFQ designed to assess dietary intake (Lamont et al, 2000;Titan et al, 2001;Cade et al, 2007;Linseisen et al, 2007). In doing so, it was recognized that although the EPIC FFQ had been validated in a UK-adult population, this had not included adults aged 85 years and above.…”
Section: Limitations Guiding Choice Of Methodsmentioning
confidence: 99%
“…If, however, as in the Newcastle 85 þ study, the aim is to assess total diet (foods, energy and a wide range of nutrients), the number of foods included in the FFQ has to be extensive. The European Prospective Investigative Study of Cancer (EPIC) FFQ was chosen as an extensively validated and widely utilized FFQ designed to assess dietary intake (Lamont et al, 2000;Titan et al, 2001;Cade et al, 2007;Linseisen et al, 2007). In doing so, it was recognized that although the EPIC FFQ had been validated in a UK-adult population, this had not included adults aged 85 years and above.…”
Section: Limitations Guiding Choice Of Methodsmentioning
confidence: 99%
“…Various studies have investigated the effects of individual socioeconomic trajectories over time on cardiovascular diseases (Davey Smith, Ben-Shlomo, & Lynch, 2002;Lamont, Parker, White, Unwin, Bennett, Cohen et al, 2000). However, to our knowledge only few studies have focused on the socioeconomic transition from active life to retirement (Wolfson, Rowe, Gentleman, & Tomiak, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…This supports previous findings of a lack of an association between, in particular, birth weight and future cardiovascular disease and metabolic syndrome risk, in the Thousand Families cohort. 11,12 However, experiencing childhood in a post-war environment, including the rationing of food, may have resulted in reduced variability in dietary disadvantage and less severe material disadvantage than cohorts born in the pre-war period. It is also possible that different results may have been obtained had other measures of fetal growth, such as ponderal index, been available to this investigation.…”
Section: Discussionmentioning
confidence: 99%
“…A previous investigation using data from this cohort suggested that the dietary questionnaire may have resulted in the under-reporting of dietary energy intake. 11 Other studies have conversely noted an over-reporting of energy intake, 22,23 suggesting that results concerning dietary intake should be viewed with caution. Further, it is likely that crosssectional measures of dietary intake would not be the most appropriate when investigating metabolic factors in an overweight or obese population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation